From Viewpoint to Reverse Metaphorization: An Analysis of Deliberate Visual Metaphors in Lifelong Learning - N. V. Mongilyova; Y. S. Talybova (Научный диалог)
This study investigates the deliberate use of visual metaphors on a university website. The research material comprises images featured in thematic sections related to lifelong learning (LLL). Special attention is given to the viewpoint as a marker of deliberateness in visual metaphor and a key element in constructing the connotation of the image. The objective of this research is to unveil the interpretative function of the viewpoint in photographs depicting lifelong learning. The analytical methodology is based on a combination of methods and techniques derived from theories of conceptual, primary, and deliberate metaphors, adapted for the purposes of this study. It is established that the upward-pointing perspective in visual messages about lifelong learning serves as a means to convey qualitative characteristics of the interactions between the central figures in the images. Through examples, it is demonstrated that the target domain of LIFELONG LEARNING is represented using the source domain of INTERPERSONAL RELATIONSHIPS. It is found that, based on universal knowledge of the value of social connections and emotional support, the authors of the images intentionally activate the metaphorical projection UNIVERSITY — PEOPLE WHO UNDERSTAND THE ADULT STUDENT. Furthermore, it is revealed that manipulation of the viewpoint generates the phenomenon of reverse metaphorization and leads to an inversion of conceptual domains (ADULT STUDENTS — UNIVERSITY).